Back Cover: Thermally stable poly(3‐hexylthiophene): Nonfullerene solar cells with efficiency breaking 10%. Issue 5 (24th October 2022) - Gao, Mengyuan; Liu, Yang; Xian, Kaihu; Peng, Zhongxiang; Zhou, Kangkang; Liu, Junwei; Li, Saimeng; Xie, Fei; Zhao, Wenchao; Zhang, Jidong; Jiao, Xuechen; Ye, Long
Abstract : With the aid of mixing thermodynamics and kinetics quenching principles, the top efficiency of over 10% and the record‐high T 80 lifetime of > 6000 hours are realized for low‐cost P3HT solar cells. In article number e190, Long Ye and co‐workers combined various characterization techniques to illustrate how to construct such low‐cost, efficient, and thermally stable organic solar cells.